TRANSFORMASI KEPEMIMPINAN PEMBELAJARAN KEPALA SEKOLAH DALAM PENGUATAN BUDAYA MUTU DAN IMPLEMENTASI KURIKULUM MERDEKA DI SEKOLAH DASAR - Rumiyadi, arif; Maghdhuroh, Umi; Sobirin, Mukhammad; Darsinah; Wafrotur Rohmah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to explore the transformation of principals’ instructional leadership in strengthening quality culture and implementing the Merdeka Curriculum in elementary schools. A qualitative approach with a case study design was employed. Participants consisted of principals, teachers, curriculum coordinators, school supervisors, and school committee members selected through purposive sampling. Data were collected through semi-structured interviews, observations, and document analysis, and analyzed using the interactive model of Miles, Huberman, and Saldaña. Data trustworthiness was ensured through source triangulation, method triangulation, member checking, and audit trails. The findings reveal that the transformation of instructional leadership occurs through the development of a school quality vision, the strengthening of quality culture through professional learning communities, the management of Merdeka Curriculum implementation as an organizational change process, and the application of collaborative leadership in addressing implementation challenges. Principals act as change agents by promoting teachers’ professional development, fostering a culture of reflection, and encouraging instructional innovation. The study concludes that the successful implementation of the Merdeka Curriculum is strongly influenced by principals’ ability to build an adaptive, collaborative, and quality-oriented organizational culture.